MODERN APPROACHES TO THE TREATMENT OF RICKETS. (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This article explores the modern approaches to the treatment and prevention of rickets, a pediatric condition caused by deficiencies in vitamin D, calcium, or phosphorus. The article delves into the etiology and pathogenesis of the disease, detailing its clinical manifestations and diagnostic evaluation. The primary focus is on contemporary treatment methods, including vitamin D, calcium, and phosphorus supplementation, sunlight exposure, nutritional intervention, physical therapy, and surgical intervention for severe cases. Additionally, the article emphasizes the importance of preventive measures such as prenatal care, neonatal supplementation, public health initiatives, and food fortification. The comprehensive discussion highlights the necessity of early diagnosis and intervention to prevent the long-term complications of rickets and promote optimal bone health in children.